Sport-based physical activity recommendations and modifications in C-reactive protein and arterial thickness - Cayres, Suziane Ungari [UNESP] (2018)
We analyzed the effects of 1 year of engagement in ≥ 300 min/week of organized sports on inflammatory levels and vascular structure in adolescents. The sample was composed of 89 adolescents (11.6 ± 0.7 years old [43 boys and 46 girls]), stratified according to engagement in ≥ 300 min/week of sport practice during at least 12 months of followup (n = 15, sport practice; n = 74, non-sport practice). Arterial thickness (carotid and femoral) was assessed by ultrasound scan, while high sensitive C-reactive protein levels were used to assess inflammatory status. Trunk fatness (densitometry scanner), biological maturation (age at peak height velocity), blood pressure, and skipping breakfast were treated as covariates. Independently of body fatness and biological maturation, the group engaged in sports presented a higher reduction in C-reactive protein (mean difference −1.559 mg/L [95%CI −2.539 to −0.579]) than the non-sport group (mean difference −0.414 mg/L [95%CI −0.846 to 0.017]) (p = 0.040). There was a significant relationship between changes in C-reactive protein and changes in femoral intima-media thickness in the non-sport group (r = 0.311 [95%CI 0.026 to 0.549]).